2019
DOI: 10.1109/access.2019.2938420
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Flow Field of Ionic Wind Induced by Corona Discharge in a Multi-Needle-to-Net Electrode Structure Under Direct-Current Voltage

Abstract: The morphologies and velocity of ionic wind induced by direct-current (DC) corona discharge were experimentally measured. DC voltage was applied to short air gaps of high-voltage electrode-needle electrode and grounding electrode-net electrode to generate coronas, so as to allow the generation of ionic wind induced by corona discharge. The purpose of the study is to optimise the multi-needle-to-net electrode structure to improve the velocity of the ionic wind and keep it in a relatively stable state. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The ionic wind speed increases with the increase of voltage and decreases with the increase of needle spacing. Lv et al found that increasing the voltage amplitude can increase the velocity of the ionic wind [24], which is consistent with our experimental results.…”
Section: A Measurement Results Of Lonic Wind Speedsupporting
confidence: 93%
“…The ionic wind speed increases with the increase of voltage and decreases with the increase of needle spacing. Lv et al found that increasing the voltage amplitude can increase the velocity of the ionic wind [24], which is consistent with our experimental results.…”
Section: A Measurement Results Of Lonic Wind Speedsupporting
confidence: 93%
“…The results indicate that, in both three-needle and fourneedle layouts, the ion wind velocity exhibits a trend of initial decrease followed by an increase with the widening electrode spacing. Lv et al [19] investigated the multi-needle-net ionic wind generator and the effect of the needle distribution and the grid side length on the wind velocity. It was found that as the grid side length was 0.85 mm, the maximum wind velocity of ionic wind is 3.5 m s −1 , which is 3 and 1.28 times that of the grid side length of 2 mm and 0.425 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…HVEF thawing is an emerging nonthermal and energy-saving thawing technology that is a feasible alternative to pyrolysis thawing. In the process of high-voltage electric field thawing, electrons and positive ions move towards the two opposite electrodes under the action of electric field force, driving the movement of air molecules, thus forming ionic wind [15]. A large number of particles produce a complex collision process with the surface of the material, which occurs in the transfer and transformation of energy, increasing the kinetic energy of the water molecules and the heat transfer in and around the material, thus accelerating the thawing of the material.…”
Section: Introductionmentioning
confidence: 99%